Ion Implantation-Modified Fluorine-Doped Tin Oxide by Zirconium with Continuously Tunable Work Function and Its Application in Perovskite Solar Cells - Dong Han; Wu, Cuncun; Zhao, Yunbiao; Chen, Yi; Xiao, Lixin; Zhao, Ziqiang (ACS APPLIED MATERIALS & INTERFACES, 2017)
In recent years, perovskite solar cells have drawn a widespread attention. As an electrode material, fluorine-doped tin oxide (FTO) is widely used in various kinds of solar cells. However, the relatively low work function (WF) (similar to 4.6 eV) limits its application. The potential barrier between the transparent conductive oxide electrode and the hole transport layer (HTL) in inverted perovskite solar cells results in a decrease in device performance. In this paper, we propose a method to adjust WF of FTO by implanting zirconium ions into the FTO surface. The WF of FTO can be precisely and continuously tuned between 4.59 and 5.55 eV through different dopant concentration of zirconium. In the meantime, the modified FTO, which had a WF of 5.1 eV to match well the highest occupied molecular orbital energy level of poly(3,4-ethylenedioxylenethiophene):polystyrene sulfonate, was used as the HTL in inverted planar perovskite solar cells. Compared with the pristine FTO electrode-based device, the open circuit voltage increased from 0.82 to 0.91 V, and the power conversion efficiency increased from 11.6 to 14.0%.